ANALISIS PERKEMBANGAN TEKNOLOGI DOMPET DIGITAL DALAM MEMFASILITASI TRANSAKSI CASHLESS DI INDONESIA - Monalisa Effendy; Cindy Patricia Kadir; Michelle Patricia Wijaya; Dorie Pandora K (CV. Denasya Smart Publisher, 2026)
The use of technology has changed how people make payments, with more people using digital methods instead of cash. A popular innovation in this development is the digital wallet, which allows users to store money and make payments, transfers, and purchases through mobile applicationsThis article analyzes at how digital wallet technology helps support cashless transactions in Indonesia. The discussion focuses on ease of use, security, technology support, and barriers to adoption. This study was conducted through a survey of digital wallet users, mainly students who have used these services for cashless transactions. Data were collected through a questionnaire and analyzed using statistical tests. The results show that digital wallets play an important role in supporting cashless transactions because they are fast, accessible, and provide transaction history. Digital wallets also work with QRIS, Indonesia’s national QR code payment standard, which makes digital payments easier to use across different platforms. However, there are still several challenges in using digital wallets. Some users still have limited digital literacy, concerns about data security, and limited internet access. This article provides a foundation for further research on digital payment behavior in Indonesia. Digital wallets have become an important part of cashless transactions because they offer convenience, speed, and security. Their use is expected to continue growing as digital payment technology develops and as people become more familiar with digital financial services.